2008
DOI: 10.1007/s12185-008-0061-z
|View full text |Cite
|
Sign up to set email alerts
|

Decreased risk of acute graft-versus-host disease following allogeneic hematopoietic stem cell transplantation in patients with the 5,10-methylenetetrahydrofolate reductase 677TT genotype

Abstract: Polymorphism in 5,10-methylenetetrahydrofolate reductase (MTHFR), a central enzyme in folate metabolism, has been shown to affect the sensitivity of patients to folate-based drugs such as methotrexate. In this study, we investigated whether a common single nucleotide polymorphism at position 677 in the donor or recipient's MTHFR gene affects the risk for acute graft-versus-host disease (GVHD) following allogeneic hematopoietic stem cell transplantation (HSCT) from HLA-identical sibling donors when the recipien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…2 Previous investigations have revealed that several single-nucleotide polymorphisms (SNPs), which impact on individual immune response to infections and inflammatory reactions are associated with SCT outcomes including the risk of acute GVHD. [3][4][5][6][7][8][9][10][11][12] IL-17, also known as IL-17A, is the hallmark cytokine of a new T-helper subset termed Th17. [13][14][15][16] gdT cells, macrophages and neutrophils are sources of IL-17 as well.…”
Section: Introductionmentioning
confidence: 99%
“…2 Previous investigations have revealed that several single-nucleotide polymorphisms (SNPs), which impact on individual immune response to infections and inflammatory reactions are associated with SCT outcomes including the risk of acute GVHD. [3][4][5][6][7][8][9][10][11][12] IL-17, also known as IL-17A, is the hallmark cytokine of a new T-helper subset termed Th17. [13][14][15][16] gdT cells, macrophages and neutrophils are sources of IL-17 as well.…”
Section: Introductionmentioning
confidence: 99%
“…Of all methotrexate's candidate genes previously examined, MTHFR, in particular the non-synonymous C677T (rs1801133) and the A1298C (rs1801131) polymorphisms, has received great attention but yielded conflicting results. 18,23,24,[29][30][31]46 In this study, associations were found between MTHFR genetic status and grade II-IV acute GvHD; none, however, remained positive for severe acute GvHD after correction for multiple testing. Based on our data, it is suggested that the SNP associated with grade II-IV acute GvHD herein are either: (i) associated with a less severe form of the disease (grade II), and/or (ii) the lower MAF (<20%) of these variants did not allow us to demonstrate their associations with grade III-IV acute GvHD occurring at a frequency of 15% in our cohort.…”
Section: Discussionmentioning
confidence: 87%
“…[26][27][28] So far, only a few studies have addressed such an important phenotype-genotype relationship, although genetic variations in the gene coding for methylenetrahydrofolate reductase (MTHFR) enzyme have received great attention. 18,[22][23][24][29][30][31][32][33] As the inter-individual variability in GvHD occurrence among HSCT patients may be, at least partly, related to the genetic diversity of genes involved in the bioavailability and in the metabolism of methotrexate/cyclosporine A, we tested in this study whether selected single nucleotide polymorphisms (SNP) located in loci encoding molecules implicated in the methotrexate/cyclosporine A metabolic and transport pathways could influence the incidence of GvHD in HSCT recipients.…”
Section: Introductionmentioning
confidence: 99%
“…Later studies also reported an association between recipient MTHFR SNP 677T* and a decreased risk of aGVHD. 19,46 Studies on thymidylate synthase (TS), another folate-dependent enzyme involved in DNA replication, also demonstrate the potential importance of copy number variation and its influence Genetic contributions to GVHD C Ting et al on disease progression. The TS enhancer region (TSER) is made up of 28 base pair repeats.…”
Section: Candidate Gene Studiesmentioning
confidence: 99%